Gender diversity and silence - Herrejón, Elvira Mejia (Revista Hipótese, 2016)
This article comes up from the following question: what potential and challenges facing schools by silencing gender diversity? The goal is to identify and discuss how the school reinforces social inequality by silencing gender diversity. Therefore, it resorts to books, monographs and articles in which authors such as Orlandi, Raymond and Zizek talk about the various types of silencing; while voices as Pêcheux, Louro, Stoller, Butler, among others, bring notions of subject, ideology and identity to sketch an idea about prejudice and the role of schools in relation to gender diversity.